Linear Drucker-Prager yield criterion calibration for polypropylene under multiaxial load - Adam Kasprzak (eXPRESS Polymer Letters, 2025)
This study focuses on calibrating the linear Drucker-Prager yield criterion for polypropylene under multiaxial loading conditions, using the Arcana fixture to achieve a wide range of triaxiality states. The Drucker-Prager criterion has been adapted for polymers, composites, and metals due to its ability to reflect the influence of hydrostatic pressure on yield stress. This study employs the Arcana fixture, which allows for testing flat plate samples under various angles, thereby simulating different stress states from pure shear to biaxial tension. Additionally, uniaxial compression tests were conducted to extend the range of triaxiality. The material used in this study is Sabic 83MF10, a polypropylene polymer. Samples were prepared by injection moulding and cut to specific dimensions. Tests were performed using a universal testing machine with the Arcana fixture, and the results were analysed to determine the yield strength, pressure, and triaxiality for each sample. The results showed a linear relationship between von Mises stress and hydrostatic pressure, with a friction angle (β) of 20.65° and material cohesion (d) of 27.81. The numerical simulations in Abaqus confirmed the validity of the Drucker- Prager model, accurately reflecting the moment of yielding for the tested samples.